Principal Leadership as a Quality Culture Motivator - Mustajab Mustajab; Chuen Lee; Jansee Jansee (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2021)
Quality improvement is becoming increasingly important for an educational institution as an effort to gain better control through its actions. The principal is a leader with the authority to regulate everything in a school institution. For the duties and responsibilities of school leaders to become real, presumably, school principals need to understand, explore and apply several concepts of management science first - these have been developed by thinkers in the business world, namely TQM (Total Quality Management) or Integrated Quality Management - later applied in education. Implementation of education needs to pay attention to the characteristics, aspirations, and needs of the community. Education should be able to provide a contextual response according to the global context. In other words, various efforts to bring together multiple parties with interests or stakeholders so that access to the formulation of policies and decision-making concerning equity and expansion of services, quality, relevance, and efficiency of education management.